2005
DOI: 10.1002/adfm.200400406
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Electrodissolution of Polyelectrolyte Multilayers: A Platform Technology Towards the Surface‐Initiated Delivery of Drugs

Abstract: A novel method for the electrochemical dissolution of polyelectrolyte multilayers from the surface of an electrode for applications in controlled drug delivery is reported. Biodegradable and biocompatible multilayer films based on poly(L‐lysine) and heparin have been selected as a model system, and have been built on an indium tin oxide semiconductor substrate. The build‐up and dissolution processes of the multilayers is followed by electrochemical optical waveguide light mode spectroscopy. The formation and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(116 citation statements)
references
References 81 publications
(90 reference statements)
3
113
0
Order By: Relevance
“…Desorption experiments beginning after 5 and 10 min of adsorption, i.e., before the continuous regime, exhibit characteristic time constants of 220 and 240 min, respectively (based on exponential fits). After 90 min of adsorption, i.e., within the continuous regime, the time constant is initially 160 min and decreases to 140 min when the potential is increased, at 1 h of desorption, to 1.7 V. Previous studies have shown similar desorption of LbL films (19,20).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Desorption experiments beginning after 5 and 10 min of adsorption, i.e., before the continuous regime, exhibit characteristic time constants of 220 and 240 min, respectively (based on exponential fits). After 90 min of adsorption, i.e., within the continuous regime, the time constant is initially 160 min and decreases to 140 min when the potential is increased, at 1 h of desorption, to 1.7 V. Previous studies have shown similar desorption of LbL films (19,20).…”
Section: Resultsmentioning
confidence: 62%
“…The influence of an applied electric potential on the adsorption of charged macromolecules (mainly proteins) has been the subject of several previous investigations (19,20,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Although most of these studies note an influence of substrate potential on adsorption, changes are typically within a factor of two or so, and to our knowledge no continuous adsorption has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[108][109][110][111][112] The insulin could be released from an electrode coated with an insulin-containing LbL film in response to an applied electric potential, because the pH around the electrode surface would be acidified by the electrolysis of H2O. However, the operating variables, such as pH, ionic strength, and the magnitude of electrode potential, have to be carefully addressed, because some drugs can be electrochemically oxidized or reduced at an electrode.…”
mentioning
confidence: 99%
“…LbL films have been used for constructing molecular architectures [11][12][13], stimuli-sensitive systems [2,[14][15][16][17], optical and electrochemical devices [5,10,[18][19][20][21][22], and controlled release systems [23][24][25][26][27][28].…”
Section: Open Accessmentioning
confidence: 99%